2021
DOI: 10.1186/s12916-020-01895-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sex hormones and risk of conventional and serrated precursors of colorectal cancer in postmenopausal women

Abstract: Background Sex hormones have been suggested to play a role in colorectal cancer (CRC), but their influence on early initiation of CRC remains unknown. Methods We retrospectively examined the associations with risk of CRC precursors, including conventional adenomas and serrated polyps, for plasma estrone, estradiol, free estradiol, testosterone, free testosterone, sex hormone-binding globulin (SHBG), and the ratio of estradiol to testosterone among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Whether or not sex hormones and adiposity contribute to SSL risk in young women remains unclear. Such a link between sex hormones and early colorectal carcinogenesis has been suggested in a previous study by Hang et al; however, specific associations for SSLs were not explored [36]. Although the diverticular disease was not associated with SSL detection in our study, there was an association between diverticular disease and adenomas in our univariate analysis and also in previous studies and meta-analyses [2,37,38].…”
Section: Other Risk Factorssupporting
confidence: 47%
“…Whether or not sex hormones and adiposity contribute to SSL risk in young women remains unclear. Such a link between sex hormones and early colorectal carcinogenesis has been suggested in a previous study by Hang et al; however, specific associations for SSLs were not explored [36]. Although the diverticular disease was not associated with SSL detection in our study, there was an association between diverticular disease and adenomas in our univariate analysis and also in previous studies and meta-analyses [2,37,38].…”
Section: Other Risk Factorssupporting
confidence: 47%
“…One possible mechanism to explain this phenomenon was the interaction of sex hormones and their regulators in CRC. The sex hormones were suggested as contributors for gender disparity in incidence and mortality of CRC [ 54 , 55 , 56 , 57 ]. Notably, despite its ambiguous and contradictory role in CRC, testosterone was suggested to be involved in CRC development and prognosis [ 56 , 58 ], and the androgen was suggested to regulate MMPs (MMP-2) and the cellular processes of intimal hyperplasia [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Because endogenous testosterone has been previously associated with prostate, colorectal and male breast cancer, they will be referred as hormone-associated cancers, HRCs, when they are combined. [4][5][6][7][8][9][10][11] Colorectal cancer is investigated as a hormone-associated cancer and not as a hormonedependent or hormone-caused cancer; therefore, this potential hormone-cancer relationship has potential translational applications for preventive diagnosis, risk stratification and treatment. 6,8,9,11 A retrospective cohort study that emulated an intent-to-treat analysis on 95,820 participants found a similar incidence of total cancer, prostate, colorectal and postmenopausal breast cancers among those who used metformin compared with those who used sulfonylureas.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Colorectal cancer is investigated as a hormone-associated cancer and not as a hormonedependent or hormone-caused cancer; therefore, this potential hormone-cancer relationship has potential translational applications for preventive diagnosis, risk stratification and treatment. 6,8,9,11 A retrospective cohort study that emulated an intent-to-treat analysis on 95,820 participants found a similar incidence of total cancer, prostate, colorectal and postmenopausal breast cancers among those who used metformin compared with those who used sulfonylureas. 1 A recent meta-analysis of 18 cohort studies did not show an association between metformin and prostate cancer.…”
mentioning
confidence: 99%